Votian Village Feasts in the Context of Russian Orthodoxy - Västrik, Ergo-Hart (Estonian Literary Museum, the Estonian National Museum and the University of Tartu, 2008)
This article considers Votian village feasts that evidently belong to the sphere of Christian folk religion. Village feasts are analysed as expressions of collective activity in pre-industrial rural society that enclosed certain religious, social and economic functions. This phenomenon of celebrating collectively certain days of church calendar, which included ritual activities in village chapels or other local sanctuaries, common meals and heavy drinking as well singing and dancing in the course of 3–4 days, was a part of common Russian Orthodox tradition shared by several ethnic groups throughout North-West Russia in the second half of the 19th century and the beginning of the 20th century. Despite the fact that this phenomenon was familiar to the wider community of Russian Orthodox believers, there were obviously certain local characteristics and variation typical to Votian tradition. However, Votain village feasts are studied in the article in the context of Russian Orthodoxy, without favouring assumed pre-Christian elements of the Finno-Ugric religions.